Modulation of early and late event-related potentials by emotion - Hart, Sarah J.; Lucena, Nathaniel; Cleary, Katherine M.; Belger, Aysenil; Donkers, Franc C. (Frontiers in Integrative Neuroscience, 2012)
Although emotionally salient stimuli influence higher order information processing, the relative vulnerability of specific stages of cognitive processing to modulation by emotional input remains elusive. To test the temporal dynamics of emotional interference during executive function, we recorded event-related potentials (ERPs) while participants performed an effortful anticipation task with aversive emotional and neutral distracters. Participants were presented with a modified delayed Stroop task that dissociated the anticipation of an easier or more difficult task (instructional cues to attend to word vs. color) from the response to the Stroop stimulus, while aversive and neutral pictures were displayed during the delay period. Our results indicated a relative decrease in the amplitude of the contingent negative variation (CNV) during aversive trials that was greater during the early anticipatory phase than during the later response preparation phase, and greater during (the more difficult) color than word trials. During the initial stage of cue processing, there was also significant interaction between emotion and anticipatory difficulty on N1 amplitude, where emotional stimuli led to significantly enhanced negativity during color cues relative to word cues. These results suggest that earlier processes of orientation and effortful anticipation may reflect executive engagement that is influenced by emotional interference while later phases of response preparation may be modulated by emotional interference regardless of anticipatory difficulty.